2012
DOI: 10.1007/978-3-642-35606-3_38
|View full text |Cite
|
Sign up to set email alerts
|

Computer Education’s Teaching-Learning Methods Using Educational Programming Language Based on STEAM Education

Abstract: STEAM is an acronym of Science, Technology, Engineering, Arts, and Mathematics. To realize the STEAM education, the factors on how to interrelate and integrate science, technology, engineering, art, and mathematics as well as the factors that are needed in realizing the STEAM education in creativity in addition to the considered factors in contents need to be decided, which in reality, makes the creation of STEAM materials into a system science or system engineering. This paper analyzed the statuses of STEAM e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 8 publications
1
18
1
7
Order By: Relevance
“…Recently, STEAM (science, technology, engineering, arts, and mathematics) education has been spreading and used in various regions and grades [19][20][21]. STEAM is an emerging educational model of how the traditional academic subjects of science, technology, engineering, arts, and mathematics can be organized into a framework by which to plan an integrative curriculum [22].…”
Section: Steam Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, STEAM (science, technology, engineering, arts, and mathematics) education has been spreading and used in various regions and grades [19][20][21]. STEAM is an emerging educational model of how the traditional academic subjects of science, technology, engineering, arts, and mathematics can be organized into a framework by which to plan an integrative curriculum [22].…”
Section: Steam Educationmentioning
confidence: 99%
“…STEAM education is similar to the latter definition and emphasizes the integration of those five subjects. STEAM education does not entail a part of education but refers to the overall paradigm from professional learning to lifelong learning [19,22]. There are several interesting approaches for STEAM education.…”
Section: Steam Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Curriculum developers, and educational supervisors can benefit from global developmental initiatives; the most recent of which was the integration of Science, Technology, Engineering and Mathematics (STEM); and the integration between Science, Technology, Engineering, Arts and Mathematics (STEAM), that are considered as the latest initiatives of the integration of the various topics with teaching through an interdisciplinary approach. Studies about these initiatives revealed that students enjoy this approach in a way that increased their motivation due to what they produce through the learning activities they carry out (Namje and Yeonghae, 2015). Going deeply into utilizing these initiatives could lead to a development in the whole school curriculum producing a holistic integrative curriculum that hides the manual nature of knowledge which students have negative attitudes towards, particularly in Jordan.…”
Section: The Pve Teachersmentioning
confidence: 99%
“…This enables it to generate and remove the application sessions for the application services after obtaining authorization from the platform, and it functions to generate and remove service sessions for the service functions of the platform. The detailed requirements are as follows [ 10 , 11 , 12 , 13 ]: The platform should be able to generate new application sessions for authorized application services. The platform should be able to provide a unique identifier to the application session of an authorized application service.…”
Section: Review Of Secure Iot Environmentmentioning
confidence: 99%